The Lepcitanian landscape across the ages: the survey between Ras el-Mergheb and Ras el-Hammam (2007, 2009, 2013). (7th November 2016) - Munzi, Massimiliano; Felici, Fabrizio; Matoug, Jabar; Sjöström, Isabella; Zocchi, Andrea
Abstract: Since 2007, the Archaeological Mission of Roma Tre University has conducted surveys in the territory of Lepcis Magna, in a peri-urban area between Ras el-Mergheb and Ras el-Hammam. To date, 168 sites have been surveyed. From the analysis of this data collection can be drawn a synthesis of the landscape's evolution from the Hellenistic to the end of the Ottoman period (including the analysis of battlefields and military structures related to the Italo-Turkish War and World War I). As elsewhere in Tripolitania, the Roman productive and settlement system was based on the villae and farms with torcularia for olive (and wine) production. However, the ancient suburban landscape was here characterised by local limestone quarry activities and funerary monuments, the research on which has given significant new data. The Late Antique and medieval periods, with their conjunctures of growth and contraction, as well as the Karamanli/Ottoman phase have been analysed for their agricultural peculiarities and forms of settlement. The Late Antique and medieval defensive system ( gsur, the Ras el-Hammam and Ras el-Mergheb castles) and the Ottoman religious landscape (marabouts or 'shrines', today almost completely demolished) have also been taken into consideration. Abstract : منذ عام 2007، قامت بعثة آثار جامعة روما تري بدراسات مسحية في أراضي لبدى الكبرى، في المنطقة شبه الحضرية التي تقع بين راس المرقب وراس الحمام . وقد تم مسح 168 موقعاً حتى تاريخه . يمكننا أن نتوصل إلى تصور لتطور الطبيعة من العصر الهلنستي حتى نهاية العهد العثماني من تحليل هذه البيانات، بما فيها تحليل لأراضي المعارك والأبنية العسكرية المرتبطة بالحرب التركية الإيطالية والحرب العالمية الأولى . كما في مناطق أخرى من طرابلس، فإن النظام الإنتاجي والاستيطاني الروماني كان مبنياً على الفيلات (المنازل المنفردة) وعلى المزارع التي تحتوي على معاصر "طرقلارية" لإنتاج زيت الزيتون (والنبيذ). ومع هذا، فإن طبيعة مناطق الضواحي القديمة كانت تتميز بأنشطة مقالع الحجر الكلسي والنصب التذكارية الجنائزية، وقد قدمت البحوث العديد من المعلومات الجديدة والهامة. إن العصور القديمة والعصور الوسطى، بما فيها من تزامن للنمو والإنكماش الاقتصادي، وأيضاً الفترة الكرمنلي / العثمانية، قد تم تحليلها جميعاً من أجل تفسير خصائصها الزراعية والاستيطانية. إن نظام الدفاع في العصور القديمة والوسطى (قصور، قلعتي راس الحمام وراس المرقب ) والطبيعة الدينية العثمانية (المربوط أو الضريح، التي تم تدميرها بالكامل تقريباً) قد تم أخذها بعين الاعتبار أيضاً.